Experimental and numerical investigation on cooling characteristics of Gifford-McMahon pulse tube cryocooler. Issue 2 (23rd February 2023) - Panda, Debashis; Satapathy, Ashok K; Sarangi, Sunil K.
ABSTRACT: In this paper, an experimental investigation is conducted to investigate the cool-down behavior of single-stage Gifford-McMahon type pulse tube cryocooler. Nine different cold head configurations of pulse tube cryocooler have been fabricated with different aspect ratios of regenerator and pulse tube to investigate their effect on the cooling process. Additionally, experimental investigation have been conducted to conceive the impact of operating parameters like mean pressure, pressure ratio on minimum refrigeration temperature, and cooling capacity. The influence of orifice and double-inlet valve opening rates on the performance parameters of pulse tube cryocooler has been investigated. A transient one-dimensional computational model of the pulse tube cryocooler is adopted to predict the theoretical refrigeration performance. In the one-dimensional computational model, the governing equations for compressible flow are solved iteratively to predict the basic fluid flow and heat transfer behaviors. It is noticed that the optimum value of the orifice valve opening to achieve maximum cooling capacity and minimum refrigeration temperature strongly depends on the geometrical parameters. The minimum refrigeration temperature and maximum cooling capacity occur at different values of orifice valve opening in each configuration. The orifice valve opening is found to be a more influential parameter on cooling capacity over the double inlet valve opening.